PENGARUH DOSIS PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL MENTIMUN (Cucumis sativus L.) PADA TANAH ULTISOL(The Effect of Chiken Manure on Growth and Yield of Cucumber (Cucumis sativus L.) at Ultisols) - . Bertua; . Irianto; . Ardiyaningsih (Bioplantae, 2012)
This research aim is to observe the effect of chiken manure on cucumbergrowth and yield, cultivar Mercy F1. Research was conducted at AgricultureTeaching and Research Farm. This experiment was design in RandomizedComplete block design. The treatment are six doses of chiken manure (k0 = 0ton ha-1, k1 = 2.5 ton ha-1, k2 = 5 ton ha-1, k3 = 7.5 ton ha-1, k4 = 10.0 ton ha-1,k5 = 12.5 ton ha-1). The parameter observes are plant dry weight, timeflowering, amount of male flower, the ratio of between male and femaleflower and yield component. Research result showed that there was significanteffect between the treatments. The highest dry weight was achived at 10ton/ha. The fastest time of flowering was achieved at 10 ton/ha. The highestcucumber yield was achieved at 10ton/ha, but there were no significant effectbetween 10 ton/ ha and 7, 5 ton/ha dan 12,5 ton/ha doses.Key words : Cucumber, chiken, male flower.